Women, politics, and power : a global perspective - Paxton, Pamela Marie; Hughes, Melanie M. (Los Angeles : Pine Forge Press, 2007)
"This book provides a clear, detailed, and current introduction to women's political representation across a wide range of countries and regions. Using broad statistical overviews and detailed case study accounts, the authors document both historical trends and the contemporary state of women's political strength in diverse countries. No other book offers such a thorough and multidisciplinary synthesis of research on women's political power around the world."--BOOK JACKET.
1. Introduction to women in politics -- 2. Women struggle for the vote : the history of women's suffrage -- 3. Women struggle for representation : accessing positions of power -- 4. Explaining the political representation of women - culture and social structure -- 5. Explaining the political representation of women - politics -- 6. Explaining the political representation of women - overarching factors -- 7. Do women make a difference? -- 8. All regions are not created equal -- 9. Middle of the pack : women and politics in the United States -- 10. Where do we go from here? : and how do we get there?
Includes bibliographical references (p. 318-348) and index.
Keywords: Women -- Political activity; Women -- Political activity -- Cross-cultural studies; Representative government and representation